PEMODELAN CROSSFLOW MIKROFILTRASI LARUTAN XANTAN BERDASARKAN ANALISIS DIMENSIONAL - Ika Amalia Kartika, E.rliza Noor dan Danu Ariono (Jurnal Teknologi Industri Pertanian, 2006)
AbstractThe present paper provides a model based on dimensional analysis that gives the basis for design of crossflow microfiltration processes. This gives the permeate flux (Jv) in terms of pressure drop across the filtration membrane P and the velocity v of crossflow of the feed fluid in the membrane tubes. The model is compared with experimental results of xanthan solution. The model has certain similarities with previous ones and can be used for unit optimization.Keywords : microfiltration, crossflow, xanthan, dimensional analysis